Implementation of Psychoeducation Program: Body Identification and Sex Education for Early Childhood: Implementasi Program Psikoedukasi: Pengenalan Tubuh danPendidikan Seks untuk Anak Usia Dini - Zahro, Elmy Bonafita; Yusainy, Cleoputri; Rachmayani, Dita (Universitas Lancang Kuning, 2025)
Even though sex education is still considered taboo, it is an essential thing for children to protect their private body parts. This psychoeducation aims to provide knowledge about the body and how to keep sexual organs healthy, targeting children aged 5 to 6 years. The population of this study were students of Kindergarten B Permata Iman 2 Malang City. The research method used was experimental design (n=64, girls 51.56%) with paired sample t-test statistical analysis techniques. The results show that providing sexual education through storytelling picture books and posters can significantly increase their knowledge about private body parts. The instruments used in this pilot study are considered easy to understand. They can be used as reference material, which needs to be adapted to the local cultural wisdom of each region. Apart from that, it is important to provide sexual education to children from an early age to prevent inappropriate actions.